Barriers and facilitators for developing a prehospital emergency care system evaluation tool (PEC-SET) for low-resource settings: a qualitative analysis - Truls Østbye; Marcus Ong; Catherine A Staton; Pin Pin Pek; Anjni Joiner; Audrey L Blewer; Meilya Silvalila; Gayathri Devi Nadarajan (BMJ Open)
Objectives Strengthening of emergency care systems, including prehospital systems, can reduce death and disability. We aimed to identify perspectives on barriers and facilitators relating to the development and implementation of a prehospital emergency care system assessment tool (PEC-SET) from prehospital providers representing several South and Southeast (SE) Asian countries.Design We conducted a qualitative study using focus group discussions (FGD) informed by the Consolidated Framework for Implementation Research (CFIR). FGDs were conducted in English, audioconferencing/videoconferencing was recorded, transcribed verbatim and coded using an inductive and deductive approach. Participants suggested specific elements to be measured within three main ‘pillars’ of disease conditions proposed by the research team of the tool being developed (cardiovascular, trauma and perinatal emergencies).Setting We explored the perspectives of medical directors in six low-income and middle-income countries (LMICs) in South and SE Asia.Participants A total of 16 participants were interviewed (1 Vietnam, 4 Philippines, 4 Thailand, 5 Malaysia, 1 Indonesia and 1 Pakistan) as a part of 4 focus groups.Results Themes identified within the four CFIR constructs included: (1) Intervention characteristics: importance of developing an contextually specific tool, need for generalisability, trialling in one geographical area or with one pillar before expanding; (2) Inner setting: data transfer barriers, workforce shortages; (3) Outer setting: underdevelopment of EMS nationally; need for further EMS system development prior to implementing a tool and (4) Individual characteristics: lack of buy-in by prehospital personnel. Elements proposed by participants included both process and outcome measures.Conclusions Through the CFIR framework, we identified several themes which can provide a basis for codeveloping a PEC-SET for LMICs with local stakeholders. This work may inform development of quality improvement tools in LMIC PEC systems.